Digital Product Valuation - Syamsu Alam; Andi Samsir (Universitas Negeri Makassar, 2023)
Why Digital Product Valution, Important? These are trends indicate a positive outlook for the digital product industry and highlight the importance of digital product valuation in determining the value of these products. So, Digital product valuation is essential for businesses and entrepreneurs who are involved in the development and distribution of digital products. Some reasons why digital product valuation is importanT that is strategic planning, pricing strategy, investment decisions, intellectual property protection, competitive analysis, financial reporting, and etc. digital product refers to any product or service that is delivered electronically through digital channels, such as the internet or mobile devices. This article will discuss why digital product valuation is important. differences between digital and non-digital products, the differences in their valuation methods, and a simulation using CAGR of digital product valuation in Python.